THU0435 DAS-28 Remission and Improvements in Skin Disease over 3 Years of Treatment with Apremilast: Results from The Palace 3 Study in Dmard/biologic-Experienced Active PsA Patients. (15th July 2016) - Edwards, C.J.; Blanco, F.J.; Crowley, J.; McIlraith, M.; Shah, K.; Teng, L.; Birbara, C.A.
Abstract : Background: Treatment goals for active psoriatic arthritis (PsA) include long-term control of both skin and joint symptoms. Achievement of remission in 28-joint count Disease Activity Score (DAS-28) using C-reactive protein (CRP), clinically important changes in DAS-28 (CRP), reduction in swollen joint count (SJC), or decrease in skin disease may be used as goals of treatment. 1 PALACE 3 (NCT01212770 ) included PsA patients with active joint disease with an active skin lesion at the time of enrollment. Objectives: Assess long-term treatment responses across PsA manifestations in patients treated with apremilast (APR) for 3 years. Methods: Patients were stratified by baseline DMARD use (yes/no) and psoriasis involvement of the body surface area (<3%/≥3%) and randomized (1:1:1) to placebo (PBO), APR 30 mg BID (APR30), or APR 20 mg BID (APR20). After a PBO-controlled phase of 24 wks, all patients were treated with APR30 or APR20 and could enroll in long-term follow-up. Efficacy assessments in years 2 and 3 were conducted at Wks 65, 78, 91, 104, 117, 130, 143, and 156. Results: 505 patients were randomized and received ≥1 dose of study medication (PBO: n=169; APR30: n=167; APR20: n=169). A total of 89% (249/281) of patients starting the third year of APR therapy completed the Wk 156 visit. Patients treated with APR30 demonstrated sustained decreases in disease activity at Wk 156, as shown by mean decreases in DAS-28 (CRP) of −1.58; 79.1% achieved a good/moderate EULAR response and 41.0% achieved DAS-28 (CRP) remission. Sustained relief across PsA manifestations, including SJC, a marker of inflammation, was also demonstrated (Table ); at Wk 156, APR30 resulted in a mean 78.3% decrease in SJC, 65.5% of patients had a swollen joint count of 0 or 1. Decreases in disability and maintenance of functionality were demonstrated by sustained decreases in HAQ-DI scores (Table ). Continued effect on skin disease was shown by decreases in skin involvement, as measured by the PASI; 54.7% of APR30 patients had a baseline PASI >5 and 27.3% had a baseline PASI >10; at 156 wks, 64.7% had a PASI <3, and 83.8% had a PASI of ≤5. PASI-75 and PASI-50 also signified clinically significant relief (Table ). No new safety concerns were identified after 156 wks of APR treatment. During Wks >104 to ≤156 of APR exposure, adverse events (AEs) occurring in ≥5% of patients were nasopharyngitis and urinary tract infection; most AEs were mild or moderate in severity. Serious AEs occurred in 7.8% of APR patients during Wks >104 to ≤156, similar to rates seen for the earlier study periods; few discontinuations due to AEs (2.1%) occurred over Wks >104 to ≤156. Conclusions: Over 156 wks, among patients continuing in the study, APR demonstrated sustained and clinically important improvements in PsA signs/symptoms, including physical function and associated psoriasis. APR was generally well tolerated and continued to demonstrate an acceptable safety profile with long-term use. References: Gossec et al. Ann Rheum Dis. 2015 Dec 7. doi: 10.1136/annrheumdis-2015-208337. [Epub ahead of print]. Disclosure of Interest: C. Edwards Grant/research support from: Celgene Corporation, Pfizer Inc, Roche, Samsung, Consultant for: Celgene Corporation, Pfizer Inc, Roche, Samsung, Speakers bureau: Abbott, Glaxo-SmithKline, Pfizer Inc, Roche, F. Blanco Grant/research support from: Celgene Corporation, J. Crowley Grant/research support from: AbbVie, Amgen, Celgene, Janssen, Merck, and Pfizer, Consultant for: AbbVie, Amgen, Speakers bureau: AbbVie, M. McIlraith Employee of: Celgene Corporation, K. Shah Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, C. Birbara Grant/research support from: Amgen, Bristol-Myers Squibb, Incyte, Eli Lilly, Merck, Pfizer Inc